PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS KELAS V SD MELALUI MODEL KONTEKSTUAL (CTL) - Cucu Cucu (COLLASE (Creative of Learning Students Elementary Education), 2022)
This study aims to improve student learning outcomes in social studies learning for fifth-grade elementary school through a contextual model (CTL). The subjects in this study were the fifth-grade students of SDN Bunisari as many as 40 students. The method of data collection was done through test techniques in the form of learning outcomes test questions and non-tests in the form of observation sheets and interviews. This classroom action research was carried out in two cycles, each cycle having systematic steps consisting of action planning, implementation and observation, and reflection. The results of this study indicate that the use of the contextual model (CTL) can improve student learning outcomes in social studies learning for fifth-grade elementary school. In addition, student activity in learning increased. The student's response to learning was very positive. Thus, learning at SDB Bunisari will be maximized if the optimal contextual model (CTL) is used.